Performance Evaluation and Optimization of Chiller Systems: A Data-Driven Approach to Enhancing Energy Efficiency - Rupdin Marbun; Teddy Ardiansyah; Nofirman Nofirman (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
Chiller systems account for a significant portion of energy consumption in industrial and commercial HVAC operations, often exceeding 50% of total power usage. However, inefficiencies such as elevated condenser pressure, inadequate heat transfer, and excessive compressor workload contribute to increased energy demand. This study presents a comprehensive performance evaluation of water-cooled centrifugal chiller systems based on 30 operational test scenarios. Key efficiency indicators—including Coefficient of Performance (COP), Specific Energy Consumption (SEC), and isentropic efficiency—were analyzed to identify performance gaps. The results revealed COP values ranging from 1.92 to 4.07, with an average between 2.8 and 3.2, indicating suboptimal performance relative to industry benchmarks (COP > 4). SEC values between 1.07 and 1.25 kW/ton further highlight opportunities for energy optimization. High condenser pressure (>7.5 barg) and negative subcooling (-4.1 K to 0 K) were identified as major contributors to inefficiency. The study emphasizes that optimizing water flow rates and maintaining proper heat exchanger conditions can significantly improve system performance. Unlike previous research relying on AI or IoT-based diagnostics, this work adopts a practical, data-driven approach, offering actionable insights for facility managers seeking to enhance energy efficiency and operational reliability.